TOPICS IN MEDICAL EDUCATION ELECTIVE BLOCK: A STUDY USING DELPHI METHOD - Geraldo Geraldo; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: Problematic practices performed by doctors and clinical phase students often be found in the workplace settings. Common problems related to team working is the highest rated problems. To overcome this problem, we designed an elective course, Medical Education block (ME) and have implemented the course since 2014. This study aimed to find topics in ME which were meaningful toward medical student’s practices. Methods: A Delphi method were utilized. The experts were the subjects themselves to acknowledge that they were the participants of the ME block, other elective blocks, and clerkship. There were 21 respondents consisted of 2012, 2013 and 2014 bathces. All the subjects were in their clerkship or at the end of their education. They were divided into two groups: who enrolled in ME (n=10), and other blocks (n=11). The questionnaire was consisted of three parts. The first part listed 5 main topics with responses of agree/disagree. The second part listed the same topics, but subjects needed to response the weight on each topic. The last part listed 27 topics in ME Block that might or might not relate to clerkship. Responses were given in agree/disagree. Results: Using two-rounded Delphi method, we found the average of rate of agreement (roa) on the first round was 88% and the second was 81%. There were only 2 statements of the second part which had roa >70%. Thus, the second part went to the 2nd round together with the 3 statements of the third parts. Finally, there were only 2 statements of the second parts achieved roa and there were 2 topics left undecided of the third part. Conclusion: Few topics which were proven useful for medical students were personal education, medical education research, and professionalism. Keywords: practices, medical education, elective course